High‐Performance and Industrially Viable Nanostructured SiOx Layers for Interface Passivation in Thin Film Solar Cells. Issue 3 (10th March 2021) - Cunha, José M. V.; Oliveira, Kevin; Lontchi, Jackson; Lopes, Tomás S.; Curado, Marco A.; Barbosa, João R. S.; Vinhais, Carlos; Chen, Wei-Chao; Borme, Jérôme; Fonseca, Helder; Gaspar, João; Flandre, Denis; et al.
Abstract : Ultrathin Solar Cells In article number 2000534, José M. V. Cunha and co‐workers applied two SiOx passivation architectures in ultrathin CIGS solar cells. Both passivation approaches resulted in devices with a higher performance compared to a reference non‐passivated device. The potential to use SiOx as passivation material, deposited by a high throughput industrial technique based in microelectronics processing, yields promising results towards high‐performance low‐cost ultrathin CIGS solar cells.